Effect of Dispersoids and Intermetallics on Hardening the Al-Si-Cu-Mg Cast Alloys - J. Hernandez-Sandoval; M. H. Abdelaziz; A. M. Samuel; H. W. Doty; F. H. Samuel (Advances in Materials Science and Engineering)
The principal aim of the present research work was to compare the role of dispersoids Al2O3 (∼15 μm average particle size) and SiC (∼15 μm average particle size) with that offered by Zr- and Ni-based intermetallics (∼35–70 μm average particle size) on the hardening of cast aluminum 354 alloy (9.1% Si, 0.12% Fe, 1.8% Cu, 0.008% Mn, 0.6% Mg, and 87.6% Al) at ambient temperature. There is no observable poisoning effect on the refinement of grain size after the addition of Zr to the alloys investigated in this study. The tensile test results were examined in light of the microstructural features of the corresponding alloy samples. The contribution of the added dispersoids or Ni and Zr alloying elements on the tensile properties of the 354 alloys was determined employing ∆P plots (where P = Property, UTS, YS, or %El), using the base alloy (in the as-cast condition) as a reference point. The tensile results were supported by investigating the precipitation-hardening phases using scanning and transmission electron microscopy as well as examining the fracture surfaces of selected conditions applying field emission scanning electron microscopy. The results show that, in all cases, Al2Cu phase is the main hardening agent. The contribution of about 1.5 vol% of SiC or Al2O3 to the strength of the base alloy is higher than that offered by Zr- and Ni-based intermetallics, under the same aging treatment.